Oncostatin M promotes excitotoxicity by inhibiting glutamate uptake in astrocytes: implications in HIV-associated neurotoxicity. Issue 1 (December 2016) - Moidunny, Shamsudheen; Matos, Marco; Wesseling, Evelyn; Banerjee, Santanu; Volsky, David; Cunha, Rodrigo; Agostinho, Paula; Boddeke, Hendrikus; Roy, Sabita
Abstract Background Elevated levels of oncostatin M (OSM), an interleukin-6 cytokine family member, have been observed in HIV-1-associated neurocognitive disorders (HAND) and Alzheimer's disease. However, the function of OSM in these disease conditions is unclear. Since deficient glutamate uptake by astrocytes is instrumental in HAND-associated neurotoxicity, we hypothesized that OSM impairs glutamate uptake in astrocytes and thereby promotes neuronal excitotoxicity. Methods Primary cultures of mouse cortical astrocytes, neurons, microglia, and BV2 cell line were used. The expression of glutamate transporters (GLAST/EAAT1 and GLT-1/EAAT2) was investigated using real-time PCR and Western blot, and their activity was assessed by measuring3 H-d -aspartate uptake. Neuronal toxicity was measured using the colorimetric MTT (3-(4, 5-dimethylthiazol-2-yl-) 2, 5-diphenyltetrazolium bromide) assay and immunocytochemistry. A chimeric HIV-1 that infects murine cells (EcoHIV/NL4-3-GFP virus (EcoHIV)) was used to investigate whether the virus induces OSM, OSM receptor (OSMR)-β, glycoprotein 130 (gp130), GLT-1, GLAST (mRNA and protein), and OSM release (ELISA) in cultured BV2 cells, primary microglia, or astrocytes. Statistical analyses of the data were performed using one-way ANOVA (to allow multiple comparisons) and two-tailed Student'st test. Results OSM treatment (10 ng/mL) time-dependently reduced GLAST and GLT-1 expression and inhibited3 H-d -aspartate uptake in cultured astrocytes in a concentration-dependent manner, an effect prevented by the Janus kinase (JAK)/signal transducers and activators of transcription (STAT)3 inhibitor AG490. Down-regulation of astrocytic glutamate transport by OSM resulted in NMDA receptor-dependent excitotoxicity in cortical neurons. Infection with EcoHIV induced OSM gene expression and protein release in BV2 cells and microglia, but not in astrocytes. Conversely, EcoHIV caused a fivefold increase in OSMR-β mRNA (but not gp130) and protein in astrocytes, but not in microglia, which did not express OSMR-β protein. Finally, astrocytic expression of GLAST gene was unaffected by EcoHIV, whereas GLT-1 mRNA was increased by twofold. Conclusions We provide first evidence that activation of JAK/STAT3 signaling by OSM inhibits glutamate uptake in astrocytes, which results in neuronal excitotoxicity. Our findings with EcoHIV suggest that targeting OSMR-β signaling in astrocytes might alleviate HIV-1-associated excitotoxicity.